2021
DOI: 10.1101/2021.08.18.456736
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subpopulations of soluble, misfolded proteins commonly bypass chaperones: How it happens at the molecular level

Abstract: Subpopulations of soluble, misfolded proteins can bypass chaperones within cells. The scope of this phenomenon and the lifetimes of these states have not been experimentally quantified, and how such misfolding happens at the molecular level is poorly understood. We address the first issue through a meta-analysis of the experimental literature. We find that in all quantitative protein refolding-function studies, there is always a subpopulation of soluble but misfolded and less-functional protein that does not f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…A second possibility is that chaperones can identify these states but ultimately cannot repair them, targeting them for degradation. The first scenario has recently been investigated by O’Brien and co-workers (Halder et al, 2021), who found computationally that E. coli isochorismate synthase (EntC), enolase (Eno), Galactitol-1-phosphate dehydrogenase (GatD), MetK, and purine nucleoside phosphorylase (DeoD) are prone to form near-native entangled states that bypass GroEL. In agreement, our study identifies Eno and DeoD as chaperone nonrefolders (as for the others: EntC had too low coverage for inclusion; MetK is GroEL-fastidious; GatD was not detected in intrinsic refolding experiments but fully refolded in all chaperone experiments, supporting previous work showing its misfolded states rapidly aggregate (Kerner et al, 2005)).…”
Section: Discussionmentioning
confidence: 99%
“…A second possibility is that chaperones can identify these states but ultimately cannot repair them, targeting them for degradation. The first scenario has recently been investigated by O’Brien and co-workers (Halder et al, 2021), who found computationally that E. coli isochorismate synthase (EntC), enolase (Eno), Galactitol-1-phosphate dehydrogenase (GatD), MetK, and purine nucleoside phosphorylase (DeoD) are prone to form near-native entangled states that bypass GroEL. In agreement, our study identifies Eno and DeoD as chaperone nonrefolders (as for the others: EntC had too low coverage for inclusion; MetK is GroEL-fastidious; GatD was not detected in intrinsic refolding experiments but fully refolded in all chaperone experiments, supporting previous work showing its misfolded states rapidly aggregate (Kerner et al, 2005)).…”
Section: Discussionmentioning
confidence: 99%
“…Only a small number of mechanisms intrinsic to a protein's primary structure are known to cause monomeric protein misfolding (Table 1). Recently, high-throughput, coarse-grained simulations of protein synthesis and folding of the E. coli proteome have suggested there exists an additional widespread mechanism of misfolding [1][2][3] . Proteins can populate off-pathway misfolded states that involve a change in entanglement 1 .…”
Section: Introductionmentioning
confidence: 99%
“…The misfolded states observed in the aforementioned simulations involved either the gain of a non-native entanglement (i.e., the formation of an entanglement that is not present in the native ensemble, Table S1) or the loss of a native entanglement (i.e., an entanglement present in the native state fails to form, Table S1) [1][2][3] . This newly predicted class of misfolding offers an explanation for the decades old observations that non-functional protein molecules can persist for long-time scales in the presence of chaperones and not rapidly aggregate nor be degraded [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations